Serum Paraoxonase-1 Levels are Significantly Decreased in the Presence of Insulin Resistance - Gateva, A.; Assyov, Y.; Tsakova, A.; Kamenov, Z. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Paraoxonase-1 (PON1) is an extracellular esterase contributing to the anti-atherogenic and anti-inflammatory properties of HDL and has a protective role in the progression of atherosclerosis. The aim of the present study was to compare serum paraoxonase-1 levels between obese subjects with prediabetes and normal glucose tolerance.Methods: In this study were included 76 patients with mean age 50.7±10.7 years, divided into 2 age and BMI-matched groups – group 1 with obesity without glycemic disturbances (n=38) and group 2 with prediabetes (n=38). Oral glucose tolerance test (OGTT) with measurement of immunoreactive insulin was performed in all participants and levels of PON1 were measured using ELISA method.Results: There was only a tendency towards higher PON1 levels in patients with prediabetes compared to controls. However, individuals with insulin resistance had significantly lower levels of PON1 compared to those without. The levels of PON1 showed a negative correlation with the blood glucose on 120th minute of OGTT, fasting IRI, HOMA index, BMI, WSR, WHR and particularly with waist circumference and positive with HDL-cholesterol.Conclusions: The levels of PON1 are similar in patients with and wthout prediabetes, but are significantly decreased in patients with insulin resistance and correlate with anthropometric markers of visceral adiposity.
Keywords: prediabetes; cardiovascular complications; paraoxonase; insulin reisistance